Mediation Effect Of Customer Satisfaction Between Promotion Mix Elements And Customer Buying Behavior In Education Sector Of Ethiopia - Kant, Shashi; Adula , Metasebia (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Present investigation conducted to check the mediation effect of customer satisfaction between promotion mix elements and customer buying behavior in education sector of Ethiopia. The researchers employed mixed method research strategy and cross sectional sequential explanatory research design. In addition to this, archival data was collected from the educational universities public relation offices. Sampling method used was purposive and simple random sampling to get the sample from the targeted population. Lastly, AMOS version 26 and SPSS vs22 were used for data analysis. The Kaiser-Meyer-Olkin test was used to measure of sampling Adequacy. Mahalanobis' distance (MD) as a statistical measure based on a chi-square distribution was employed to check the extent to which cases are adjusted with multivariate outliers. SEM model fitness results showed the complete mediation i.e the entire (or total) effect of Promotion Mix Elements on a Customer Buying Behavior is transmitted through Customer Satisfaction. Thus, the Promotion Mix Elements have no direct effect on the Customer Buying Behavior; rather, its entire effect is indirect. Thus, mediation role of Customer Satisfaction was really happening in a given model, but the total effect is significant simply because the sample size is very large, or assumptions for the test of the total effect were met.